The impact of religious affiliation on the unmet need for family planning of women in the Philippines - Gan, Stephanie Natalie C.; Tee, Clarice Kimberley M.
Background: Religions prescribe moral codes that limit the choices individuals make for themselves, even in the aspect of reproductive health decisions. In the Philippines, approximately 96 percent of the population identify to have a religious affiliation and thus are highly influenced by religious doctrine. This secular state has constantly struggled with the influence and power that religious institutions like the Catholic Church hold, even within politics. In order for the Philippines to meet their international pledges United Nations (UN) with respect to their 2030 Sustainable Development Goals (SDGs) and be successful in meeting targets set by the Philippine Development Plan 2017-2022, population control and reproductive health for women must be improved. To do this, it is important to identify the barriers that keep women from having full control over their decisions related to their reproductive health. This critical assessment of the Unmet Need for Family Planning (FP) can help policy-makers understand the crucial elements in drive this indicator, so that the government may better monitor and evaluate the Philippine population and health programs.